Optimizing Organizational Psychology: Reconstructing the Transformational Leadership Role of School Principals as Murabbi in Building an Innovation Ecosystem in Technology - Musslifah, Anniez Rachmawati; Khusnuliawati, Hardika; Cahyani, Rusnandari Retno (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
This research aims to reconstruct the leadership role of school principals in the digital age, moving from the traditional managerial paradigm to the Murabbi leadership model. Specifically, this study explores how Day Care principals implement transformational leadership to build a sustainable innovation ecosystem in a technology-based education environment. This study uses a qualitative approach with multiple case study designs. This research was conducted at Al-Ghazi Day Care. Data collection was conducted through semi-structured in-depth interviews with principals, innovation coordinators, and senior teachers, as well as participatory observation of curriculum development meetings and technology-based learning activities. Data are analyzed using thematic analysis to identify patterns, strategies, and challenges in leadership practice. Key findings show that the reconstruction of leadership roles occurs through three main dimensions: (1) Technopedagogical Vision, where school principals not only adopt technology but also embed Islamic pedagogical vision in it; (2) Collaborative Empowerment, which is shifting authority from hierarchical to facilitative by creating a safe space for teachers to experiment and fail; and (3) Cultivation of Digital Spirituality, which is to guide the school community to use technology ethically and meaningfully according to Islamic values. The role of Murabbi is manifested in guiding, inspiring, and serving as a role model in innovation, not just in managing resources. This study concludes that the Murabbi leadership model offers a practical framework for transformational leadership in modern Islamic educational institutions. This model allows the principal not only to be an innovation manager but also a character builder and an architect of an ecosystem that fosters creativity authentically and spiritually. The practical implication of this research is the need for a leadership development program that integrates technological competencies with Islamic pedagogical leadership values.